2009
DOI: 10.1038/sj.bjc.6605412
|View full text |Cite
|
Sign up to set email alerts
|

Metronomic chemotherapy with daily, oral etoposide plus bevacizumab for recurrent malignant glioma: a phase II study

Abstract: BACKGROUND: We evaluated bevacizumab with metronomic etoposide among recurrent malignant glioma patients in a phase 2, open-label trial. METHODS: A total of59 patients, including 27 with glioblastoma (GBM) and 32 with grade 3 malignant glioma, received 10 mg kg À1 bevacizumab biweekly and 50 mg m À2 etoposide daily for 21 consecutive days each month. The primary end point was a 6-month progression-free survival, and secondary end points included safety and overall survival. Vascular endothelial growth factor (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
87
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 193 publications
(92 citation statements)
references
References 45 publications
3
87
0
2
Order By: Relevance
“…PFS-6 rates ranged between 28 and 50.3% and median OS between 6.7 and 9.7 months. Other experimental agents that were combined with bevacizumab are etoposide [98], the mTOR inhibitor temsirolimus [99], the EGFR-targeted tyrosine kinase inhibitor erlotinib [100], the multikinase inhibitor sorafenib [101], the histone deacetylase inhibitors panobinostat [102] or vorinostat [103].…”
Section: Bevacizumab Monotherapy and Combination Regimensmentioning
confidence: 99%
“…PFS-6 rates ranged between 28 and 50.3% and median OS between 6.7 and 9.7 months. Other experimental agents that were combined with bevacizumab are etoposide [98], the mTOR inhibitor temsirolimus [99], the EGFR-targeted tyrosine kinase inhibitor erlotinib [100], the multikinase inhibitor sorafenib [101], the histone deacetylase inhibitors panobinostat [102] or vorinostat [103].…”
Section: Bevacizumab Monotherapy and Combination Regimensmentioning
confidence: 99%
“…Several phase 2 trials of bevacizumab-based combinations have also been reported for recurrent glioblastoma (Table 1), 27,28,32, including bevacizumab with irinotecan, irinotecan plus cetuximab, irinotecan plus carboplatin, etoposide, fotemustine, sorafenib, temozolomide, erlotinib, and temsirolimus. 27,28,32,[38][39][40][41][42][43][44][45][46][47] In addition, several retrospective studies have also been reported combining bevacizumab and irinotecan; carboplatin; carboplatin and cetuximab; carboplatin, etoposide, and ifosfamide; lomustine; carmustine; etoposide; or temozolomide. [48][49][50][51][52][53][54][55][56][57][58] Although these small studies are not easily compared due to their size and various patient populations, the consensus to date has been that no combination significantly surpasses the outcomes of bevacizumab monotherapy for recurrent glioma.…”
Section: Early Study Of Bevacizumab In Patients With Recurrent Glioblmentioning
confidence: 99%
“…Addition of metronomic etoposide in bevacizumab treated patients with recurrent glioma had no additional benefit compared to bevacizumab alone but resulted in increased toxicity [71].…”
Section: Other Chemotherapeutic Combinationsmentioning
confidence: 99%